Brian Cherney as Scholar and Creative Artist - Elliott, Robin (Intersections)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 2017)
While best known as a composer, Cherney has also been active in music scholarship. His doctoral thesis in musicology was on German music criticism during the Weimar era, but in his later career he has made important and timely interventions into Canadian music studies. Among his publications are articles on John Weinzweig and Pierre Mercure, as well as a monograph on Harry Somers, who is the subject of his ongoing research. His course on Canadian music at McGill University has introduced many students to the serious study and understanding of composed music in Canada. This article considers Cherney’s music scholarship and speculates on how this work may have had an impact upon his creative activities as a composer.